Reduction of Carbon Emission Is Optimized During the Life Cycle of Commonly Used Force Main Pipe Materials - Alsadi, Alhossin A.; Matthews, John C. (Frontiers in Water, 2022)
With increasing attention to global warming and greenhouse gases (GHG) emissions and providing a better environment for coming generations, there is a critical need to quantify and decrease the environmental impact. Underground construction projects are one of the biggest constructions in North America; consequently, it is one of the GHG emissions' primary sources. This research focused on optimizing the carbon dioxide (CO₂) emissions for a 91 cm (36 in) diameter sewer pressure pipe with 3 m (10 ft) depth and 30 m (100 ft) length, operating at 690 kPa (100 psi) during the commonly used pipeline materials' life cycle: Cured-in-Place Pipe (CIPP), Pre-stressed Concrete Cylinder Pipe (PCCP), High-density polyethylene (HDPE) pipe, and Polyvinyl Chloride (PVC) pipe. The life operations for this study were considered 100-years. The four phases of a pipeline life cycle included in this study are fabrication, installation, operation, and disposal phases. The study results show that the CO₂ emissions have been reduced by 16% on the PCCP pipe, 4% on PVC pipe, 1% on HDEP pipe, and by 3.2% and 2.0% on CIPP lining (50 years and 100 years life expectancy, respectively).